2015
DOI: 10.2147/ceor.s76269
|View full text |Cite
|
Sign up to set email alerts
|

End-stage renal disease in autosomal dominant polycystic kidney disease: a comparison of dialysis-related utilization and costs with other chronic kidney diseases

Abstract: BackgroundAutosomal dominant polycystic kidney disease (ADPKD) is the leading inheritable cause of end-stage renal disease (ESRD) and one of the leading causes of ESRD overall. ADPKD patients differ from the overall dialysis population; however, there is little published data regarding health care costs for ADPKD patients on dialysis.MethodsThis retrospective observational cohort study was designed to quantify health care utilization and costs for ADPKD patients with ESRD who received initial services at a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 11 publications
0
21
0
1
Order By: Relevance
“…Nevertheless, the administration of Tolvaptan causes some side effects, such as polyuria and high activity of hepatic enzymes, increasing the management costs of patients [9]. Therefore, dialysis is still the main therapy for ADPKD patients, but it requires high healthcare and personnel costs and limits the life quality of patients [10]. To improve benefits and reduce healthcare costs, the use of combined compounds able to target different pathways could be an attractive purpose for the treatment of ADPKD [11].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the administration of Tolvaptan causes some side effects, such as polyuria and high activity of hepatic enzymes, increasing the management costs of patients [9]. Therefore, dialysis is still the main therapy for ADPKD patients, but it requires high healthcare and personnel costs and limits the life quality of patients [10]. To improve benefits and reduce healthcare costs, the use of combined compounds able to target different pathways could be an attractive purpose for the treatment of ADPKD [11].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 28 papers were classified initially as potentially relevant and the full papers retrieved. Of the 28 articles, 14 potential relevant papers were excluded for the following reasons: no associated endpoint events data [12,13,15,31,32]; did not compare PKD and Non-PKD patients [33][34][35]; not distinguish dialysis modalities, such as HD or PD [36,37]; only epidemiological studies about ESRD due to PKD on PD [2,4]; enrolled patients from the same cohorts [10,38]. Finally, the remaining 14 articles [9, 16-26, 39, 40] were included in our meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It may be gradually playing an important role on patients with PKD in ESRD that health care resource utilization and costs for those requiring dialysis were needed to be considered. Therapeutic interventions that can prevent or delay the progression in ESRD patients with PKD for increased dialysis-free life [33] were needed to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39] In a retrospective study in a large dialysis organization in the United States that included 1,274 patients with ADPKD and aimed to quantify healthcare expenditures and costs for ADPKD patients with ESRD, the total healthcare costs for those patients were considerable -at US$4,254 per patient per month or US$51,048 per patient-year. 37 However, the same study showed that the total costs for ESRD patients other than those with ADPKD were higher. Another study in the United States that reviewed the administrative records of a private health insurer and included 1,913 patients with ADPKD demonstrated that higher charges are associated with advanced kidney disease, as the annual medical charges …”
Section: Burden Of Adpkd Economic Burdenmentioning
confidence: 99%